Cardiac surgery and phenprocoumon therapy— Is preoperative normalization of the international normalized ratio necessary?. (18th February 2016) - Essa, Yasin; Amorim, Paulo; Färber, Gloria; Hoyer, Heike; Hofmann, Michael; Doenst, Torsten
Objectives: Patients on phenprocoumon presenting for surgery are often converted to heparin preoperatively. We assessed the impact of this conversion on outcome in cardiac surgery patients. Methods: From November 2007 to September 2013, 115 patients with phenprocoumon therapy presented for surgery and were operated either before or after the international normalized ratio (INR) had normalized (group A, INR > 1.3, n = 71; group B, INR ⩽ 1.3, n = 44 at day of surgery; group C, matched control cohort without preoperative phenprocoumon, INR ⩽ 1.3, n = 60). Results: Patients received a mix of cardiac surgical procedures (including valves, coronary artery bypass grafting, ventricular assist devices, and transplantation) without intergroup differences. Surgery was emergent in 11%, 2%, and 13% in groups A, B, and C, respectively (p = 0.2). Preoperative hospital stay was longest in group B (p < 0.01). Hospital mortality was high with 26% in group A (EuroSCORE 22 ± 22), 13% in group B (EuroSCORE 17 ± 16), and 7% in group C (EuroSCORE 10 ± 15) p < 0.01. Mean chest tube drainage (first 24 h) was lowest in group C (mean/min/max, A: 1096/350/4750 mL; B 1086/300/4100 mL; C 757/120/2170 mL, p = 0.03), and preoperative hemoglobin was highest (A: 7.5 ± 1.2, B: 7.5 ± 1.4, C: 8.1 ± 1.2 mmol/L, p = 0.01). If transfusion was required, patients in group A received more red blood cells (mean units, A: 4.5 ± 8; B: 3.5 ± 6; C: 1.5 ± 3, p = 0.02). By multivariate analysis, preoperative INR was not an independent predictor of postoperative bleeding (p = 0.8). Only low preoperative fibrinogen predicted increased chest tube drainage, independent of phenprocoumon (p = 0.01). Conclusion: Patients presenting for cardiac surgery with preoperative phenprocoumon represent a high-risk population. Bleeding complications for these patients are higher but do not seem to be influenced by preoperative INR. Our data question the need for conversion to heparin.